The Effect Of Eco-Efficiency, Green Innovation, And Sustainability Performance On Firm Value - Sari Mustika Widyastuti; Esti Tri Endarwati (UNIVED Press, 2025)
This study aims to determine the impact of eco-efficiency, green innovation and sustainability performance on firm value with a sample of companies listed on the Indonesia Stock Exchange for the 2020-2023 period in the food and beverage sector. The population is 125 companies, a sample of 33 companies was obtained. The technique used in sampling is non-probability sampling with a purposive sampling type. Firm value is proxied by Tobin's Q. Content analysis as an indicator of measuring the company's sustainability performance variables disclosed in the Annual Report and Sustainability Report, and ownership of ISO 14001 certification as an indicator of measuring the eco-efficiency variable. The analysis technique used is multiple linear regression analysis of panel data. The results of the study show that eco-efficiency and sustainable performance have a significant effect on company value. Meanwhile, green innovation does not have a significant effect on firm value.